Measurement and Spatiotemporal Evolution of High-Quality Economic Development at the County Level Based on Machine Learning Methods: A Case Study of Guangdong Province - Shuhua Liu (The International Journal of Multiphysics, 2024)
This article develops a five-dimensional evaluation system for assessing high-quality economic development at the county level, employing the entropy method to analyze economic progress in 57 counties across Guangdong Province from 2010 to 2020.Utilizing machine learning techniques, the study uncovers the spatiotemporal dynamics and regional disparities in economic development at this level within Guangdong. Findings indicate a consistent annual improvement in the quality of economic development across the counties, with growing absolute disparities that display characteristics of "club convergence." Notably, the Pearl River Delta and the eastern and western parts of Guangdong exhibit a multipolar growth pattern, with regional variances primarily driving the overall disparities in high-quality economic development at the county level in Guangdong Province.